Design and experimental validation of the high-speed counter-rotating thresher for pomegranate aril extraction - Ma, Peifeng; Zhu, Aibin; Zhang , Jing; Mao , Han; Zheng , Chunli; Huang , Jinping; Wang , Jing; Bao, Bingsheng; Gao, Chong; Li, Dangchao (International Journal of Agricultural and Biological Engineering, 2026)
This study presents the design and experimental validation of a high-speed, drum-type pomegranate thresher driven by an innovative single-drive, multi-shaft transmission system. This design integrates crushing, feeding, and threshing into a compact unit, significantly reducing mechanical complexity and energy consumption. Finite element analysis verified the structural integrity of key components under operational loads. Systematic experiments identified an optimal speed of 220 r/min, achieving a threshing efficiency of 28.6 pieces/min, a peel removal rate of 88.3%, and an aril damage rate of 12.6%. The incorporation of a pre-crushing mechanism enhanced overall efficiency by 30.6%, a performance gain analyzed as a trade-off against a manageable increase in aril damage. The device demonstrated robust adaptability, processing fresh and stored pomegranates at rates of 33.9 and 27.9 pieces/min, respectively, while revealing critical correlations between pomegranate physical properties and threshing outcomes. This work provides an efficient and scalable solution for industrial pomegranate processing and establishes a foundation for future intelligent control systems. Keywords: pomegranate, high-speed thresher, drum-type thresher, strength analysis DOI: 10.25165/j.ijabe.20261901.10057 Citation: Ma P F, Zhu A B, Zhang J, Mao H, Zheng C L, Huang J P, et al. Design and experimental validation of the high-speed counter-rotating thresher for pomegranate aril extraction. Int J Agric & Biol Eng, 2026; 19(1): 302–308.